Integrative taxonomic revision of the Xenimpia-Psilocladia-Coenina generic complex with a review of the genus Procypha Warren, 1897 stat. rev. (Lepidoptera, Geometridae, Ennominae, Gonodontini) - Stadie, Dirk; László, Gyula M.; Fiebig, Ralf (Zootaxa, 2025)
Using an integrative approach, the classification of the Afrotropical ennomine genera Xenimpia Warren, 1895, Coenina Walker, 1860, and Psilocladia Warren, 1898, is revised. As a result of the DNA barcoding combined with morphological data, eight distinct genera are delimited and characterised to include the current species content of Xenimpia, Coenina and Psilocladia: Bambenga László, Stadie & Fiebig gen. nov. (type species Xenimpia repudiosa Prout, 1915), Arebatia László, Stadie & Fiebig gen. nov. (type species Xenimpia tetracantha Herbulot, 1973), Claudimpia László, Stadie & Fiebig gen. nov. (type species Xenimpia soricina Herbulot, 1973) and Paracoenina László, Stadie & Fiebig gen. nov. (type species Coenina dentataria Swinhoe, 1904) are established. Furthermore, Xenimpia Warren, 1895 (type species: X. erosa Warren, 1895), Coenina Walker, 1860 (type species: Geometra poecilaria Herrich-Schäffer, 1854) and Psilocladia Warren, 1898 (type species: P. obliquata Warren, 1898) are retained as valid genera and the latter is excluded from the tribe Gonodontini; in addition, Procypha Warren, 1897 stat. rev. (type species P. maculosata Warren, 1897) is reinstated from synonymy with Xenimpia. As a consequence of the revised generic classification, the following new combinations are established: Bambenga repudiosa (Prout, 1915) comb. nov., Arebatia albicaput (Fletcher, 1956) comb. nov., A. angusta (Prout, 1915) comb. nov., A. burgessi (Carcasson, 1964) comb. nov., A. ceres (Karisch, 2020) comb. nov., A. chalepa (Prout, 1915) comb. nov., A. clenchi (Viette, 1980) comb. nov., A. conformis (Warren, 1898) comb. nov., A. crassimedia (Herbulot, 1996) comb. nov., A. crassipecten (Herbulot, 1961) comb. nov., A. fletcheri (Herbulot, 1954) comb. nov., A. flexuosa (Herbulot, 1996) comb. nov., A. informis (Swinhoe, 1904) comb. nov., A. kala (Herbulot, 1973) comb. nov., A. karischi (Herbulot, 1996) comb. nov., A. loile (Carcasson, 1964) comb. nov., A. loxostigma (Prout, 1915) comb. nov., A. luxuriosa (Herbulot, 1961) comb. nov., A. spinosivalvis (Herbulot, 1996) comb. nov., A. tetracantha (Herbulot, 1973) comb. nov., A. vastata (Herbulot, 1996) comb. nov., Claudimpia diaereta (Prout, 1923) comb. nov., C. misogyna (Carcasson, 1962) comb. nov., C. soricina (Herbulot, 1973) comb. nov., Paracoenina dentataria (Swinhoe, 1904) comb. nov., P. aegyptiaca (Rebel, 1906) comb. nov., P. islamitica (Amsel, 1935) comb. nov., Procypha transmarina (Herbulot, 1961) comb. nov. and P. dohertyi (Herbulot, 1961) comb. nov. Moreover, the genus Procypha is taxonomically revised, including descriptions of five new taxa (P. paradohertyi sp. nov., P. strutzbergi sp. nov., P. strutzbergi caputgalli ssp. nov., P. insolita sp. nov. and P. meyi sp. nov.) and synonymisation of Xenimpia lactesignata Warren, 1914 syn. nov. regarded as a junior synonym of X. maculosata Warren, 1897. Based on diagnostic morphology, the genus Procypha is subdivided into four species groups. The early stages of Procypha maculosata, P. dohertyi and P. strutzbergi Stadie, László & Fiebig sp. nov. are described and depicted, as well as wing patterns and genitalia of all species in this genus are figured. The paper is illustrated with two dendrograms inferred from ML genetic analyses, four distribution maps and 83 colour figures demonstrating the type species of each genus discussed and the adults, genitalia, early stages and habitats of Procypha taxa.